The Decision to Choose a Boarding House: Location Attractiveness, Service Quality, and Brand Trust - Yuli Binsya; Stivenes Tjin Siam (Universitas Bumigora, 2025)
The rapid development of Indonesia’s education sector has led to an increase in the number of universities and students. Pontianak is home to high-quality universities that attract students from within and outside the city. This has led to increased demand for student housing, especially boarding houses. This study aims to determine the influence of location attractiveness, service quality, and brand trust on students’ decisions when choosing boarding houses in Pontianak. This study used quantitative methods. The study population consisted of students who rented boarding houses in Pontianak. The sampling method used was accidental sampling, and the sample size was 130 respondents. The data for this study were collected through questionnaires, and the analysis technique used a rating scale processed using SPSS version 24. The results of this study indicate that location attractiveness and service quality have a positive and significant effect on students’ decisions to choose boarding houses in Pontianak City. However, brand trust was found to have no positive and significant effect on students’ decisions to choose boarding houses in Pontianak City. The novelty of this research lies in the finding that the brand trust variable does not dominate and influence the decision to choose a boarding house, unlike in several pre- vious studies. The implications of this research emphasize the importance of boarding house managers focusing on strategic location and service quality for tenants as factors that influence the decision to rent.